Management of Peripartum Cardiomyopathy in Severe Preeclampsia Patients in ICU - Mulyawan, Dadang; Pison, Osmond M. (CoinReads Media Prima, 2024)
Introduction: Peripartum cardiomyopathy (PPCM) is a life-threatening cardiomyopathy with left ventricular systolic dysfunction, in late pregnancy, during delivery, or in the first months postpartum, in women who have no previously identifiable cause of heart failure. Case: A 25-year-old primigravida woman with a pregnancy of 35 weeks came to the Emergency Department (ER) with symptom of severe pre eclampsia, and pulmonary edema and later underwent a cesarean section. After surgery, the patient is admitted to the ICU , and then became worsening. Echocardiography was then performed and found a decrease in left ventricular systolic function, EF 35%, posterior anterior acinetics, mild MR. The diagnosis of PPCM was established. The therapy given is drugs and a negative fluid balance is created for this patient. On day 10, the patient showed improvement in left ventricular function with EF 48%. The patient is extubated from a mechanical ventilator and moved to the internal medicine inpatient room. Conclusion: I Early diagnosis with supporting echocardiography as well as appropriate management in PPCM cases greatly determines the success of therapy in patients in the ICU.